Struktur Industri Asam Sitrat - Karsini Karsini (Jurnal Kimia dan Kemasan, 1987)
Citric acid is crystalline organic acid which is widely used in industries.The requirement of this acid tends to increase every year, following the industrial development. Along with this line, it is there for necessary to look for cheap and readily available material to fulfill the demand Citric acid fermentation is an extremely complex process so in order to obtain higher concentration of citric acid, some main factors should be taken in concentration, for example, microorganism, medium composition, aeration, ratio volume to area surface and medium strirring. In addition, the problem of citric acid industry is the waste product. Because it can make pollution if it pilled up abudantly. Actually the organic solid waste can be used for compost as organic fertilizer, and an organic solid waste can be used for home decoration and so on.